THE IMPACT OF DEBT FINANCING AND EQUITY FINANCING ON PROFIT EXPENSE RATIO OF ISLAMIC BANKS IN INDONESIA - nenden nenden; isnurhadi isnurhadi; taufik taufik (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2017)
The purpose of this study is to determine whether Equity Financing and DebtFinancing partially and simultaneously have an impact on Profit Expense Ratio, alsohow the partial effect of each financing systems affect Profit Expense Ratio. Thisresearch is causal research, also called explanatory research is the investigation of(research into) cause-and-effect relationships. The number of taken samples is two, suchas PT. Bank Muamalat Indonesia (BMI) and PT. Bank Syariah Mandiri (BSM). Thedata used in this research are secondary data from published financial statements ofBMI and BSM. The data analysis technique used is linear regression. The results of dataanalysis in this research is partially contained direct or positive relationship betweenDebt Financing and Equity Financing on Profit Expense Ratio. While the effects ofDebt Financing and Equity Financing as the independent variables (X) simultaneouslyaffect Profit Expense Ratio as the dependent variable (Y) on Islamic banks, it meansthat Debt Financing and Equity Financing simultaneously have significant impacts onProfit Expense Ratio of Islamic banks. The obtained value of coefficient ofdetermination (R2) is 0.516 or 51.6%. It means that the variation of these independentvariables, namely Debt Financing and Debt Financing, contribute effects on ProfitExpense Ratio of Islamic Banks. In accordance with the analysis result of this research,it can be seen that Equity Financing is dominant in affecting Profit Expense Ratio ofIslamic Banks compared to Debt Financing. The researcher suggests management ofIslamic banks to prioritize Equity Financing system, especially Musharaka, because thesaid financing system is the most appropriate with Islamic law to apply to muslims.Keywords : Debt Financing, Equity Financing, Profit Expense Ratio